Cultural Identity in the Digital Age: Navigating Globalization in Local Communities - Manara, Ralf; Weber, Mark (Journal of Humanities and Social Sciences (JHASS), 2023)
In the digital age, cultural identities are transforming due to the growing influence of globalization. This study explores how local communities in the United Kingdom navigate their cultural identities amidst the pervasive reach of digital platforms and global cultural narratives. The objective is to analyze the adaptive strategies employed to balance the preservation of local traditions with the adoption of global influences. Using a qualitative approach, data were collected through semi-structured interviews and thematic analysis conducted with representatives from diverse cultural communities in the UK. The findings reveal that digital platforms serve as both a challenge and an opportunity. On the one hand, they expose local cultures to homogenizing global trends, particularly affecting younger generations. On the other hand, these platforms act as powerful tools for sharing and preserving local traditions, enabling communities to reassert their cultural distinctiveness on a global stage. Discussions emphasize the critical role of digital literacy and proactive cultural policies in fostering a balanced coexistence between local and global influences. Future research could examine the intersection of cultural identity and economic factors, focusing on how creative industries in the UK leverage cultural heritage for innovation. Additionally, longitudinal studies could explore generational shifts in cultural values and practices in the digital age.